Biochemical parameters and relation to disease severity in COVID-19 patients - Çalişir, Büşra; Çöplü, Ni̇lay; Kilinç, Çeti̇n; Gülhan, Muhammet; Soylu, Veysel Garani̇; Durak, Özlem; Özcan, Esra; Özcan, Selahatti̇n; Akpulat, Uğur; Gülten, Sedat (MediHealth Academy, 2021)
Aim: In this study, we aimed to evaluated whether there is an association between the biochemistry parameters obtained from the first blood test after hospitalization of COVID 19 patients and the prognosis and severity of the disease. Thus, we planned to identify patients with a severe course at an early stage and to help physicians determine the appropriate treatment. Material and Method: The study included 106 COVID 19 patients confirmed by RT-PCR. Patients were categorized into two groups: those admitted to the hospital ward and discharged with recovery (mild cases) and those admitted directly or eventually to the intensive care unit (severe cases). Biochemical parameters of the groups were compared with the Mann Whitney-U Test, as none of the compared parameters fit the normal distribution. Results: There was no statistically significant difference between the male-female numbers and ages of the two groups. Statistically significant differences were observed in the length of hospital stay, procalcitonin, hs-troponin I, ferritin, glucose, urea, creatinine, calcium, direct bilirubin, AST, LDH and CRP values (p<0,05). However, no significant difference was found in sodium, potassium, chloride, total bilirubin and ALT tests. Conclusion: The results show that some biochemistry parameters may be used to predict the prognosis of the disease. In particular, procalcitonin, hs troponin I, LDH and CRP values seem to be moderate biomarkers of the prognosis of the disease.
Keywords: 3. Good health